Promoting sustainable development through strategies, environmental management accounting and environmental performance - Appannan, Jeya Santhini; Mohd Said, Ridzwana; Ong, Tze San; Senik, Rosmila (Wiley, 2022)
Extant research on environmental management accounting (EMA) has mainly emphasised its impact on environmental disclosures and cost measurements, while the role of EMA in environmental performance has largely been neglected. Hence, the study addressed the literature gap by applying the natural resource‐based view (NRBV) and the dynamic capabilities (DC) theory to investigate EMA as a fundamental managerial innovation mechanism that explains the relationship between environmental strategies and environmental performance. Questionnaires were used to gather data from 145 managers of ISO14001‐certified Malaysian companies. The results of the Partial Least Squares Structural Equation Modelling (PLS‐SEM) analysis demonstrated that EMA mediates the effects of pollution prevention and clean technology strategies on environmental performance but not the effect of the process stewardship strategy. The findings encourage companies to adopt specific environmental strategies to attain better environmental performance through EMA. Moreover, the results highlighted the company limitations in improving environmental performance. The study is one of the first few attempts to integrate EMA with environmental strategies through the application of the NRBV and the DC theory. Additionally, the study provides empirical evidence that efficient EMA management can be transformed into reasonable operational performance and produce positive outcomes.